2014
DOI: 10.1042/bst20140114
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the regulated assembly of SNARE complexes in adipocytes

Abstract: Insulin plays a fundamental role in whole-body glucose homeostasis. Central to this is the hormone's ability to rapidly stimulate the rate of glucose transport into adipocytes and muscle cells [1]. Upon binding its receptor, insulin stimulates an intracellular signalling cascade that culminates in redistribution of glucose transporter proteins, specifically the GLUT4 isoform, from intracellular stores to the plasma membrane, a process termed 'translocation' [1,2]. This is an example of regulated membrane traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is of interest that both the SM protein Munc18c and its cognate Qa-SNARE Syntaxin4 are phosphorylated on tyrosine residues in response to insulin. In the case of Munc18c this has been shown to regulate SNARE complex assembly at least in vitro (42,43). In response to an insulin stimulus, Munc18c exhibits >10 fold increase in tyrosine phosphorylation in 3T3-L1…”
Section: Tyrosine Phosphorylation Of Sec1/munc18 Proteinsmentioning
confidence: 98%
“…It is of interest that both the SM protein Munc18c and its cognate Qa-SNARE Syntaxin4 are phosphorylated on tyrosine residues in response to insulin. In the case of Munc18c this has been shown to regulate SNARE complex assembly at least in vitro (42,43). In response to an insulin stimulus, Munc18c exhibits >10 fold increase in tyrosine phosphorylation in 3T3-L1…”
Section: Tyrosine Phosphorylation Of Sec1/munc18 Proteinsmentioning
confidence: 98%
“…This could be highly relevant for adipocyte function, as caveolae are most prominent in adipocytes, with roles in endocytosis, cholesterol and fatty acid uptake, lipid droplet formation and signal transduction [122,123]. In follow-up studies, we then identified AnxA6-induced cholesterol imbalance to cause mislocalization and dysfunction of several cholesterol-sensitive SNARE proteins in the secretory pathway [72,73], all of which are fundamental for the metabolic response that facilitates GLUT4 translocation in adipocytes [124]. Also, recent findings from our laboratories indicate that cholesterol accumulation in late endosomes of NPC1 mutants promotes the interaction of AnxA6 with the Rab7-GTPase activating protein TBC1D15 (Rentero, Grewal and Enrich, unpublished results), which has recently been implicated in Rab7-dependent pathways that regulate GLUT4 translocation to the cell surface [125].…”
Section: Annexin Expression Patterns In Adipose Tissue and Their Pmentioning
confidence: 99%
“…Along these lines, and as discussed for AnxA6 overexpression and NPC1 deficiency above (see 2.3. ), it is tempting to speculate that late endosomal cholesterol accumulation triggered by AnxA8 downregulation might compromise adipocyte function leading to the improper performance of molecular events in caveolae [63,122,123], or related to insulin signaling and GLUT4 translocation [19,72,73,124].…”
Section: Annexin Expression Patterns In Adipose Tissue and Their Pmentioning
confidence: 99%
“…GLUT4 is the major glucose transporter in muscle and adipose tissue, which constantly cycles between the plasma membrane and intracellular membranes due to the presence of insulin. The GLUT4 endocytic and exocytic itineraries involve a complex interplay of trafficking events and intracellular signalling cascades [ 13 , 14 ]. Calcineurin can dephosphorylate cytoskeletal proteins, such as actin and tubulin [ 15 20 ], and proteins involved in endocytosis, such as dynamin and assembly protein 180 kDa (AP)180 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%